Temporal changes of NDVI for qualitative environmental assessment of mangroves: Shrimp farming impact on the health decline of the arid mangroves in the Gulf of California (1990–2010). (February 2016) - Alatorre, Luis C.; Sánchez-Carrillo, Salvador; Miramontes-Beltrán, Sonia; Medina, Ramiro J.; Torres-Olave, María E.; Bravo, Luis C.; Wiebe, Lara C.; Granados, Alfredo; Adams, David K.; Sánchez, Erick; Uc, Mario
Abstract: We assessed the temporal evolution of vegetation activity of mangroves in the Southeastern coastal of the Gulf of California (Mexico) through a multi-temporal analysis of Landsat TM images from 1990 to 2010 where time series of the Normalized Difference Vegetation Index (NDVI) were obtained. A multivariate regression analysis showed the presence of statistically significant negative trends of NDVI (low vegetation activity) in the coverage of mangrove forest, mangrove forest with pickleweed, and pickleweed; however, we did not found any meteorological variable (built time series of average minimum and maximum temperatures, and of accumulated rainfall) that controlled the observed trends. A pixel-by-pixel spatially distributed analysis of the temporal trends of NDVI, complemented by digitalization through photo interpretation of the shrimp farms present in the study area, showed a spatial relationship between the zones of greatest loss of vegetation activity (1990–2010) and the areas with greater proliferation of shrimp farms in the study area. Our study demonstrated the applicability of NDVI for the environmental assessment of mangroves. The relationship between changes in remote sensing indices and environmental variables allows for an efficient evaluation of the main environmental impacts, which can be used for coastal planning and management. Highlights: Shrimp farming are affecting arid coastal ecosystems in the Northwestern Mexico. The applicability of NDVI for the environmental assessment of mangroves. The mangrove forests in the SE Gulf of California show signs of worsening health.